2021
DOI: 10.3390/genes12101640
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Seq Revealed the Gene Expression Pattern during the In Vitro Maturation of Donkey Oocytes

Abstract: Donkeys are an important domesticated animal, providing labor, meat, milk, and medicinal materials for humans. However, the donkey population is continuously declining and even at risk of extinction. The application of modern animal production technology, such as oocyte in vitro maturation, is a promising method to improve the donkey population. In this study, we explore the gene expression patterns of donkey germinal vesicle (GV) and in vitro matured metaphase II (MII) oocytes using single cell RNA-seq of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…was also excavated in the previous reports on donkey oocytes (Li, Song, et al, 2021). This study also found that ADCY3, PDE3B, ACAA1, ACAA2, ACLY, OGDHL and other DEGs in MII oocytes were also down-regulated compared with GV stage.…”
Section: Smartsupporting
confidence: 60%
See 2 more Smart Citations
“…was also excavated in the previous reports on donkey oocytes (Li, Song, et al, 2021). This study also found that ADCY3, PDE3B, ACAA1, ACAA2, ACLY, OGDHL and other DEGs in MII oocytes were also down-regulated compared with GV stage.…”
Section: Smartsupporting
confidence: 60%
“…Transcriptome analysis during oocyte maturation has been implemented in many animals, such as sheep (Fang, Xia, et al, 2022), pigs (Fang, Wu, et al, 2022), and donkeys (Li, Song, et al, 2021). Few studies have been conducted on horse oocytes yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study made an in-depth exploration of gene expression characteristics by thoroughly comparing the similarities and differences in oocyte development during GV-MII between donkeys and cattle, sheep, pigs, and mice (Qian et al, 2019;Wang et al, 2020b;Du et al, 2021;Li et al, 2021a;Li et al, 2021b), Furthermore, the release of the newly assembled donkey reference genome and the update of bioinformatics analysis tools (Wang C. et al, 2020), allowed us to annotate donkey genes more accurately, and to obtaining more refined results. Interestingly, in terms of transcriptome characteristics, we found that the GV and MII phases formed two groups of cells with a clear dividing line (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In vicunas, 41% of oocytes matured in vitro after 27 h, which is a shorter time than for other domesticated camelids (Chaves et al, 2004). Finally, in rhinoceros, an IVM time of 36-44 h has been reported (Hildebrandt et al, 2018), which is the approximate time for horses and donkeys (Li et al, 2021). Therefore, establishing the IVM time is an initial step in obtaining oocytes suitable for fertilization.…”
Section: In Vitro Maturation Conditionsmentioning
confidence: 99%